Li-Fraumeni Syndrome in Breast Cancer: Development of Theranostic Probes on Variation of P53 - Yi, Andy; Yun, Jongwon; Lee, Jian; Park, KyuBin (Technium BioChemMed, 2024)
Li-Fraumeni Syndrome (LFS) is a hereditary condition characterized by a high predisposition to various cancers due to mutations in the p53 protein. Effectively targeting and treating this syndrome requires early detection and personalized treatment according to one’s specific nucleotide sequence. With the use of various forms of theranostics, LFS can be treated, increasing life expectancy; however, there is no absolute cure that could immediately end this syndrome. This paper delves into three different theranostic approaches: Gendicine (rAd-p53), Phesgo, and gold nanoshell poly(D, L-lactic-co-glycolic acid) nanoparticles (PLGA NPs). While each approach has limitations, PLGA nanoparticles exhibit advantages that outweigh their drawbacks, making it an attractive solution. This proposal will describe improvements to PLGA nanoparticles, which are a promising area of research for the development of new LFS treatments.